Déficit de vitamina B12 en relación con la evaluación del estado nutricional en adultos mayores del Barrio Obrapía - Armijos Carrión, Livia Carolina (2015)
Vitamin B12 is essential for DNA synthesis, maturation and development of erythrocytes, in older people the ability to absorb vitamin B12 from food decreases, the result of this is the deficiency in vitamin B12. By this reason the following objectives were stablished to determine vitamin B12, to assess the nutritional status and its relation between vitamin B12 and nutritional status in older people of Obrapía neighborhood. The study was descriptive, of cross-sectional, carried out with 51 people who had inclusion criteria, through electrochemiluminescence method for vitamin B12 and IMC to assess nutritional status. The following conclusions were obtained, 68.62% of the people had normal serum vitamin B12 and 31.37% of them had high values; within nutritional status 5.88% presented malnutrition, 33.33% underweight, finally there was no relation between low levels of vitamin B12 with malnutrition. The main recommendations were: that this study constitutes in an incentive for future studies in different cities of our country in order to obtain a data source of this vitamin that is very important, and to contribute to the improvement of lifestyle on people, and to inform about the importance of good nutrition, especially in the population of gerontology, which lead to provide a lifetime of happiness and healthy to prevent diseases and to encourage people to live an active and healthy life. Keywords: older people, Vitamin B12, nutritional state.